2009
DOI: 10.1002/ajmg.a.32640
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of the first reported case of inv dup del 20p compatible with a U‐type exchange model

Abstract: Inverted duplications with terminal deletions have been reported for an increasing number of chromosome ends. The best characterized and most frequent rearrangement reported involves the short arm of chromosome 8. It derives from non-allelic homologous recombination (NAHR) between two inverted LCRs (low copy repeats) of the olfactory receptor (OR) gene cluster during maternal meiosis. We report here on the cytogenetic characterization of the first inversion duplication deletion involving the short arm of chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 59 publications
4
24
0
Order By: Relevance
“…They did not detect a single copy region but were able to narrow down the region ''fusion site'' to $11 Kb. Wang et al [2008], using array-CGH and FISH did not identify a single copy region exceeding 100 Kb in an inv dup del 5p and neither could Leclercq et al [2009] detect a single copy segment exceeding 6 Kb using an oligo array-CGH (244 K) in an inv dup del 20p. Duplicated and deleted regions, interrupted by a very small single copy segment, have only been reported on two occasions [Ballif et al, 2003;Bonaglia et al, 2009].…”
Section: Discussion Rearrangementmentioning
confidence: 75%
“…They did not detect a single copy region but were able to narrow down the region ''fusion site'' to $11 Kb. Wang et al [2008], using array-CGH and FISH did not identify a single copy region exceeding 100 Kb in an inv dup del 5p and neither could Leclercq et al [2009] detect a single copy segment exceeding 6 Kb using an oligo array-CGH (244 K) in an inv dup del 20p. Duplicated and deleted regions, interrupted by a very small single copy segment, have only been reported on two occasions [Ballif et al, 2003;Bonaglia et al, 2009].…”
Section: Discussion Rearrangementmentioning
confidence: 75%
“…Our patient is another with a subtelomeric loss of 20p13 [Baker et al, 2002; Adeyinka et al, 2005; Leclercq et al, 2009; Stevens et al, 2009; McGill et al, 2010]. Apart from patients described in more detailed by McGill et al The others harbor deletions as a result of complex [Leclercq et al, 2009; Stevens et al, 2009] or familial rearrangements [Baker et al, 2002, Adeyinka et al, 2005]. In addition, there are previously described patients with terminal deletions of the short arm of chromosome 20 which encompass the JAG1 gene, known to cause Alagille syndrome [Krantz et al, 1997] as well as or cytogenetically visible aberrations [Schinzel, 2001].…”
Section: Discussionmentioning
confidence: 95%
“…Although 20p13 deletions may be associated with developmental delays in motor and speech, mental retardation and epilepsy at various levels of severity, and facial dysmorphism (Moutton et al, ), the typical characteristics of such cases remain enigmatic, leading to diagnostic delays. Interestingly, previous studies showed that patients who simultaneously harbored a duplication and subtelomeric deletion of 20p exhibited facial dysmorphism, psychomotor retardation, delayed development, and speech difficulties (Leclercq et al, ; Trachoo, Assanatham, Jinawath, & Nongnuch, ). However, the precise mechanisms underlying duplications and/or deletions of the 20p13 chromosome band remain unclear and require further study.…”
Section: Discussionmentioning
confidence: 99%